The abuse-related effects of pyrrolidine-containing cathinones are related to their potency and selectivity to inhibit the dopamine transporter. (November 2018) - Gannon, Brenda; Baumann, Michael; Walther, Donna; Jimenez-Morigosa, Cristian; Sulima, Agnieszka; Rice, Kenner; Collins, Gregory
Abstract Synthetic cathinones are common constituents of abused "bath salts" preparations and represent a large family of structurally related compounds that function as cocaine-like inhibitors or amphetamine-like substrates of dopamine (DAT), norepinephrine (NET), and serotonin (SERT) transporters. Preclinical evidence suggests that some cathinones (e.g., MDPV and α-PVP) are more effective reinforcers than prototypical stimulant drugs of abuse, such as cocaine or methamphetamine. Although the reinforcing potency of these cathinones is related to their potency to inhibit DAT, less is known about the pharmacological determinants of their unusually high reinforcing effectiveness. To this end, we tested the hypothesis that reinforcing effectiveness of cathinone stimulants is positively correlated with their selectivity for DAT relative to SERT. Uptake inhibition assays in rat brain synaptosomes were used to directly compare the potency of MDPV, MDPBP, MDPPP, α-PVP, α-PPP, and cocaine at DAT, NET, and SERT, whereas intravenous self-administration in rats was used to quantify relative reinforcing effectiveness of the drugs using progressive ratio (PR) and behavioral economic procedures. All cathinones were more potent at DAT than NET or SERT, with a rank order for selectivity at DAT over SERT of α-PVP > α-PPP > MDPV > MDPBP > MDPPP > cocaine. These synthetic cathinones were more effective reinforcers than cocaine, and the measures of reinforcing effectiveness determined by PR and demand curve analyses were highly correlated with selectivity for DAT over SERT. Together, these studies provide strong and convergent evidence that the abuse potential of stimulant drugs is mediated by uptake inhibition at DAT, with activity at SERT serving as a negative modulator of reinforcing effectiveness.